SUKU GOCI KELURAHAN AMPANG DINAMIKA KEHIDUPAN SOSIAL EKONOMI PEDAGANG REMPAH-REMPAH KELILING (2000-2011) - Aidil, Ahmad; Hardi, Etmi; Yulia, Refni (Pendidikan Sejarah, 2014)
This paper is about Goci TribeAmpang Village Spice Merchants Socioeconomic Dynamics from 1980 to 2011. This issue needs to be addressed, because the presence of spice merchants from the tribe in the village AmpangGoci can change the economy well. The formulation of this study as follows: (a) How Goci Tribe start to take part as spice merchants (b) How Goci Tribeâs activity as spice merchants in ( 1980-2011 ). (c) How the dynamics of Goci Tribeâs socioeconomic life as spice merchantsin ( 1980-2011 ).This research includes the study of history , and therefore this study follows the method of history namely: (1) Heuristic that is to look for and collect information from primary and secondary sources, (2) Criticism sources include internal and external criticism, namely by testing for the authenticity of the source or specified materials, (3) Interpretation that is an activity of interpreting the data that has been collected, and (4) Historiography which is the stage presentation of research results in the form of a thesis.The results showed that the spice has significant impact to the socio-economic life of the merchant, that is the rising incomes in Goci TribeAmpangVillage. The perceived impact to traders namely, first, the requirement for merchants economy is fulfilled. Second, merchants can spare some revenue from the sale of spices for savings or to buy valuable items such as gold, home furnishings and vehicles. Third, spice merchants can do upgrade to their homes to better housings , for example, from the semi-permanent housing becomes permanent. Fourth, farmers are more eager to send their children to a higher level education, such as junior high, high school, and college. Fifth, the incrementof their awareness to their health, as they Â havespare money for treatment.Â